Implementing Sustainable Islamic Higher Education Campuses: A Practical Framework - Husni, Husni; Azis, Abdul; Selamet, Selamet (Jurnal Penelitian Pendidikan Islam, 2023)
Most people know that our planet is in grave danger, but only a select few are doing something to stop the damage. Administrators at Islamic universities will find this article's framework for creating greener campuses useful. Institutional leaders must now take decisive action to rescue the planet by enacting environmentally friendly campus development programs or policies, directing environmental preservation, and building a clean, healthy, environmentally friendly, and sustainable campus. Several feasible frameworks are available for use in Islamic higher education institutions. The first step in environmental education management is the creation of an environmentally friendly curriculum, followed by the implementation of community-based education, the enhancement of the campus and surrounding environment, the implementation of an environmentally friendly support system, and finally the creation of environmental-based educational management.